The use of nanostructured films in the development of packaging for meat and meat products: A brief review of the literature. (October 2022) - Machado, Éricles Forrati; Favarin, Fernanda Reis; Ourique, Aline Ferreira
Highlights: Films containing nanoparticles were able to decrease lipid oxidation. Films containing nanoparticles can increase the shelf life of the meat products. Films containing nanoparticles were effective in combating microorganisms in food. Films containing nanoparticles may be an alternative to conventional packaging. Abstract: This review aimed at investigating the development of films containing nanoparticles for the production of packaging that can increase the conservation of meat products. In the development of the films, more research was found with natural polymers, mainly chitosan. Most of the articles used polymeric nanoparticles followed by metallic nanoparticles and the most tested products were chicken and beef. In the products, the main analysis were in relation to the lipid oxidation and the evaluation of the antimicrobial activity. Most studies showed that the films were able to decrease lipid oxidation and, consequently, increase the shelf life of the products. Regarding antimicrobial control, the films have been shown to be effective in combating various food spoilage microorganisms, especially against Staphylococcus aureus and Escherichia coli. Thus, it is concluded that the use of films containing nanoparticles in the production of packaging for meat products can be an alternative to conventional packaging. However, more research needs to be carried out in order to establish analytical techniques to detect and characterize nanoparticles in food, so that to evaluate whether the particles retain their original characteristics. In addition, the evaluation of the toxicity of nanoparticles, especially when found in the food matrix, should be investigated.